Gender differences in neuropsychological performance across psychotic disorders--a multi-centre population based case-control study. - Jolanta Zanelli; Kevin Morgan; Paola Dazzan; Craig Morgan; Manuela Russo; Izabela Pilecka; Paul Fearon; Arsime Demjaha; Gill A Doody; Peter B Jones; Robin M Murray; Abraham Reichenberg (PLoS ONE)
Background Patients with schizophrenia and other psychoses exhibit a wide range of neuropsychological deficits. An unresolved question concerns whether there are gender differences in cognitive performance. Methods Data were derived from a multi-centre population based case-control study of patients with first-episode psychosis. A neuropsychological test battery was administered to patients with a diagnosis of schizophrenia or schizoaffective disorder (N=70, 36% females), bipolar/mania (N=34, 60% females), depressive psychosis (N=36, 58% females) and healthy controls (N=148, 55% females). Generalized and specific cognitive deficits were compared. Results There was strong evidence for disorder-specific gender differences in neuropsychological performance. Males and females with schizophrenia showed similar pervasive neuropsychological impairments. In psychotic depressive disorder females performed worse than males across neuropsychological measures. Differences in neuropsychological performance between males and females with bipolar/manic disorder were restricted to language functions. Symptom severity did not contribute to the observed gender differences. Conclusions Early in the course of psychotic illness, gender related factors appear to moderate the severity of cognitive deficits in depressive psychosis and bipolar/mania patients.